A importância de um manual universitário na abadia de Alcobaça - Barreira, Catarina Alexandra Martins Fernandes (2016)
Os quatro livros das Sentenças ou Sententiarum libri IV foram redigidos entre 1156 e 1158 por Pedro Lombardo, professor na École de Notre Dame e Bispo de Paris. A seguir à Bíblia, foi a obra mais lida e comentada na Idade Media, um estatuto que manteve ate ao seculo XVI. Este best seller medieval de Pedro Lombardo como Graciano e Hugo de Sao Victor, referencias entrosadas com as opiniões de Lombardo no intuito de responder as questões teológicas significativas para a época. O exemplar manuscrito núcleo deste nosso artigo pertenceu a biblioteca da Abadia de Alcobaça (alc. 417) e revela‑se bastante interessante do ponto de vista codicológico e da sua decoração iluminada, pois levanta algumas questões no que concerne a sua origem e ligação a códices de origem francesa de meados do seculo XIII. Peter Lombard, professor at the School of Notre Dame and Bishop of Paris, wrote the four books of Sentences or Sententiarum libri IV between 1156 and 1158. Next to the Bible, it was the work most read and commented in the Middle Ages, a status that remained until the sixteenth century. This medieval best seller gathers quotes from the Bible, from the Patristic auctoritates as Saint Augustine, Lombard contemporary authors such as Gratian and Hugo of St. Victor, and the ideas of Peter Lombard in order to respond to the significant theological issues at the time. This manuscript belongs to the library of the Abbey of Alcobaça (alc. 417) and proves to be quite interesting concerning its codicological analyse and its illuminated decoration. This article aims to trace its journey, since its origin and its connection to manuscripts with a French origin in the mid‑thirteenth century.